Application of CoSe2-rGO catalyst in degradation of ofloxacin

The CoSe2-rGO catalyst effectively addresses the degradation challenges of ofloxacin in wastewater by forming a stable heterojunction with graphene oxide, achieving high efficiency and durability in treating antibiotic pollution.

CN119114110APending Publication Date: 2024-12-13XINXIANG MEDICAL UNIV +3
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411251280.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-07
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing wastewater treatment methods struggle to effectively degrade and remove ofloxacin, a third-generation fluoroquinolone antibiotic, due to its complex structure and strong toxicity, leading to environmental issues such as antibiotic resistance and bioaccumulation, and traditional catalysts using metal ions face stability and contamination challenges.

Method used

A CoSe2-rGO catalyst is prepared through a hydrothermal method, combining graphene oxide with CoSe2 to form a heterojunction composite that activates peroxymonosulfate, enhancing the degradation of ofloxacin with high efficiency and stability.

Benefits of technology

The CoSe2-rGO catalyst achieves a degradation efficiency of 97% for ofloxacin within 40 minutes, maintaining effectiveness across a wide pH range and resisting anion interference, with minimal metal leaching and long service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114110A_ABST
    Figure CN119114110A_ABST
Patent Text Reader

Abstract

The invention provides application of a CoSe2-rGO catalyst in degradation of ofloxacin, and belongs to the technical field of sewage treatment. The graphene oxide (GO) with good ion selectivity, strong mechanical property and pollution resistance is used as a carrier, the carrier is combined with the transition metal selenide through a simple hydrothermal method to form a heterojunction composite material, and the prepared CoSe2 / rGO composite catalyst is used for activating PMS, has excellent catalytic activity, stability, durability and universality, and has good application prospects. And a feasible choice is provided for green elimination of antibiotic pollution in the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment, and in particular to application of a CoSe2-rGO catalyst in the degradation of ofloxacin. Background Art

[0002] Antibiotics are a class of organic compounds that treat or inhibit bacterial infections. The complex structure, difficult degradation and strong toxicity of their secondary metabolites seriously disrupt the balance of aquatic environments and pose major challenges to environmental remediation. After being treated in sewage treatment plants, the detection limit of most antibiotics remains in the range of ppm to ppt, and they are not effectively removed, resulting in some active products surviving or being converted into more free hydrophilic forms and discharged into the water environment. Ofloxacin (OFX) belongs to the third-generation fluoroquinolone drugs and is a representative antibiotic for the treatment of respiratory tract, urogenital system and gastrointestinal tract infections. After administration, more than 25-75% of active metabolites are excreted through urine or feces, and the concentration detected in the water environment is as high as 31.7μg / L. In addition, residual OFX in the water environment can cause a series of problems such as antibiotic-resistant bacteria and / or antibiotic resistance genes, potential genotoxicity and bioaccumulation, and growth inhibition.

[0003] At present, common sewage treatment technologies are often used to degrade or remove antibiotics, such as coagulation, flocculation, solvent extraction, advanced oxidation, biodegradation, reverse osmosis, ion exchange, etc. These methods have achieved certain results to varying degrees. However, traditional treatment methods still restrict the ability to degrade antibiotics. Therefore, it is urgent to develop a green and effective method to remove residual OFX in water and reduce the negative impact on the aquatic environment.

[0004] Advanced oxidation processes (AOPs), such as photocatalysis, sulfate radical oxidation, and Fenton oxidation, are considered a promising approach for wastewater treatment. However, the asymmetric molecular structure of peroxymonosulfate (PMS, HSO5 - ) than the symmetrical peroxydisulfate (PDS, S2O82 - ) is more easily activated. PMS often involves the generation of reactive oxygen species (ROS) during the reaction process, such as hydroxyl radicals (·OH), sulfate radicals (SO4· - ), superoxide radicals (O2· - ) and singlet oxygen ( 1 O2), these active species attack the chemical structure sites of harmful pollutants and quickly crack the pollutants to achieve mineralization effect. -It has attracted much attention due to its advantages such as high redox potential (2.5-3.1V), long half-life, low pH dependence, and low toxicity of secondary metabolites. The use of PMS to activate and degrade antibiotics in wastewater has achieved remarkable results, and a large number of excellent catalysts of different types have appeared in people's field of vision. PMS can be activated by various transition metals (Ni, Co, Fe, Cu, Ag), etc., and the higher valence OO bond in HSO5- can be catalytically destroyed by the low valence state of transition metals. Therefore, the Co element in the transition metal, its Co 3+ / Co 2+ has a higher redox potential (E0 = 1.82 V), therefore, Co 2+ With Co 3+ The valence states of the solution are mutually converted and then PMS activation is achieved through interfacial charge transfer. However, materials that rely on metal ions as active centers are prone to secondary contamination (metal leaching, poor stability) and shortened catalyst life. Summary of the invention

[0005] The object of the present invention is to provide an application of a CoSe2-rGO catalyst in the degradation of ofloxacin. The prepared CoSe2 / rGO composite catalyst has excellent stability, durability and universality and a long service life.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides an application of a CoSe2-rGO catalyst in the degradation of ofloxacin. The preparation method of the CoSe2-rGO catalyst comprises the following steps:

[0008] Mixing Se powder, alkaline reagent and water to obtain a Se-containing mixed solution;

[0009] Mixing cobalt salt, EDTA-2Na and water to obtain a cobalt salt solution;

[0010] The Se-containing mixed solution is mixed with a cobalt salt solution to perform a first hydrothermal reaction to obtain CoSe2;

[0011] Graphene oxide, water and the CoSe2 are mixed to carry out a second hydrothermal reaction to obtain a CoSe2-rGO catalyst.

[0012] Preferably, the mass ratio of the Se powder to the alkaline reagent is 0.16-0.32:1.2-3.6.

[0013] Preferably, the mass ratio of the cobalt salt to EDTA-2Na is 0.48-0.95:0.34-0.73.

[0014] Preferably, the molar ratio of the Se powder to the cobalt salt is 1 to 4:1.

[0015] Preferably, the temperature of the first hydrothermal reaction is 150-180° C., and the time is 12-18 hours.

[0016] Preferably, the mass ratio of graphene oxide to CoSe2 is 50-150:100.

[0017] Preferably, the temperature of the second hydrothermal reaction is 160-180° C., and the time is 10-12 hours.

[0018] Preferably, the application method comprises: mixing the CoSe2-rGO catalyst, the OFX-containing solution and peroxymonosulfate, and degrading the resulting mixed solution.

[0019] The present invention provides an application of a CoSe2-rGO catalyst in the degradation of ofloxacin, using graphene oxide (GO) with good ion selectivity, strong mechanical properties and pollution resistance as a carrier, combining with transition metal selenide through a simple hydrothermal method to form a heterojunction composite material, using the interaction between heterojunctions to fix metal ions and reduce the risk of leakage. Moreover, GO as a carrier can improve the electron transmission effect, and the prepared CoSe2 / rGO composite catalyst is used for the activation of PMS, has excellent catalytic activity, and provides a feasible option for green elimination of antibiotic pollution in the environment.

[0020] The results of the embodiment show that the degradation efficiency of OFX by the CSR150 / PMS / Vis system under 40 minutes of illumination is 97%, and this degradation efficiency can be maintained continuously in a wide pH range (3 to 11) and with strong resistance to anion interference. The CoSe2 / rGO composite catalyst has excellent stability, durability and universality, and has great application potential in practical environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 In the figure, (ab) FESEM images of CoSe2; (c) FESEM image of GO; (d) FESEM image of rGO; (ef) FESEM image of CSR150;

[0022] Figure 2 Middle, (ac) HRTEM images of CSR150; (dh) EDS element mapping spectrum of CSR150;

[0023] Figure 3In the figure, (ab) XRD patterns of GO, rGO, CoSe2 and CoSe2 / rGO composites; (c) Raman spectra of CoSe2, GO, rGO and CSR150; (d) XPS full spectrum scan of CoSe2, rGO and CSR150; (e) C1s; (f) O1s; (g) Co2p; (h) Se3d and (i) UV-VisDRS spectra of CoSe2, rGO and CoSe2 / rGO composites;

[0024] Figure 4 (a) Catalytic degradation effect of OFX under different conditions; (b) -ln(C t / C0) as a function of reaction time during the degradation process; (c) rGO doping effect on the catalytic degradation of OFX and (d) first-order kinetic curve;

[0025] Figure 5 Effects of different conditions (a) PMS concentration; (b) catalyst dosage; (c) OFX concentration; (d) solution pH value on the degradation effect in the CSR150 / PMS / Vis system;

[0026] Figure 6 (a) The degradation effect of CSR150 catalyst on different water sources; (b) The degradation comparison of different pollutants by CSR150 catalyst; (c) The effectiveness cycle experiment of CSR150 catalyst; (d) The effect of different anions in CoSe2 / rGO / PMS / Vis system on the degradation performance of OFX. DETAILED DESCRIPTION

[0027] The present invention provides an application of a CoSe2-rGO catalyst in the degradation of ofloxacin. The preparation method of the CoSe2-rGO catalyst comprises the following steps:

[0028] Mixing Se powder, alkaline reagent and water to obtain a Se-containing mixed solution;

[0029] Mixing cobalt salt, EDTA-2Na and water to obtain a cobalt salt solution;

[0030] The Se-containing mixed solution is mixed with a cobalt salt solution to perform a first hydrothermal reaction to obtain CoSe2;

[0031] Graphene oxide, water and the CoSe2 are mixed to carry out a second hydrothermal reaction to obtain a CoSe2-rGO catalyst.

[0032] In the present invention, unless otherwise specified, the required materials or reagents are commercially available products well known to those skilled in the art.

[0033] In the present invention, the mass ratio of the Se powder to the alkaline agent is preferably 0.16-0.32:1.2-3.6, more preferably 0.32:2.4; the alkaline agent is preferably sodium hydroxide.

[0034] In the present invention, the cobalt salt is preferably CoCl2·6H2O; the mass ratio of the cobalt salt to EDTA-2Na (as a precipitant) is preferably 0.48-0.95:0.34-0.73, more preferably 0.48:0.73; the molar ratio of the Se powder to the cobalt salt is preferably 1-4:1, more preferably 2-3:1.

[0035] The present invention preferably adds an alkali reagent into water, stirs evenly, adds Se powder, and magnetically stirs for 15 minutes to form a Se-containing mixed solution; adds cobalt salt and EDTA-2Na into water, stirs for 10 minutes to form a cobalt salt solution, pours the cobalt salt solution into the Se-containing mixed solution, stirs for 5 minutes, ultrasonicates for 30 minutes, and then stirs for 10 minutes, pours the obtained mixed solution into a 100 mL polytetrafluoroethylene reactor, and performs a first hydrothermal reaction.

[0036] In the present invention, the temperature of the first hydrothermal reaction is preferably 150-180° C., and the time is preferably 12-18 hours.

[0037] After completing the first hydrothermal reaction, the present invention preferably centrifuges the obtained product, washes it with ultrapure water three times, and dries it at 60° C. for 12 h to obtain CoSe2.

[0038] In the present invention, the mass ratio of graphene oxide (GO) to CoSe2 is preferably 50-150:100, more preferably 1:1.

[0039] The present invention preferably adds GO to water, dissolves it by ultrasonication to form a yellow-brown solution, adds CoSe2, dissolves it by ultrasonication, continues stirring for 1 hour, and pours it into a 100 mL polytetrafluoroethylene reaction axe to carry out a second hydrothermal reaction.

[0040] In the present invention, the temperature of the second hydrothermal reaction is preferably 160-180° C., more preferably 180° C., and the time is preferably 10-12 h, more preferably 10 h.

[0041] After completing the second hydrothermal reaction, the present invention preferably centrifuges the obtained product at high speed, washes it with ultrapure water three times, and dries it at 60° C. for 24 h to obtain a CoSe2-rGO catalyst.

[0042] In the present invention, the application method preferably comprises: mixing the CoSe2-rGO catalyst, the OFX-containing solution and the peroxymonosulfate, and degrading the obtained mixed solution.

[0043] The present invention preferably uses a solution containing OFX as simulated wastewater.

[0044] In the present invention, the dosage ratio of the CoSe2-rGO catalyst to the OFX (ofloxacin) solution is preferably 10-30 mg:50 mL, more preferably 10 mg:50 mL, and the concentration of the OFX solution is preferably 10-40 mg / L, more preferably 20 mg / L.

[0045] In the present invention, the concentration of the peroxymonosulfate in the mixed solution is preferably 1-2 mmol / L, more preferably 2 mmol / L; the peroxymonosulfate is preferably potassium hydrogen persulfate.

[0046] The present invention has no particular limitation on the degradation time, which can be adjusted according to actual wastewater treatment needs.

[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0048] Example 1

[0049] 2.40g NaOH was added to 60mL ultrapure water and stirred evenly, and then 0.32g Se powder was added and magnetically stirred for 15min to form a Se-containing solution; 0.48g CoCl2·6H2O and 0.73g EDTA-2Na were added to 20mL ultrapure water and stirred for 10min to form a cobalt salt solution; the cobalt salt solution was poured into the Se-containing solution and mixed and stirred for 5min, ultrasonicated for 30min, and stirred for another 10min, and the obtained mixed solution was poured into a 100mL polytetrafluoroethylene reactor, heated at 180℃ for 12h, and the obtained product was centrifuged, washed with ultrapure water 3 times, and dried at 60℃ for 12h to obtain CoSe2;

[0050] 50 mg GO was added to 80 mL ultrapure water, and ultrasonically dissolved until GO was a yellow-brown solution. 0.10 g CoSe2 was added, and after ultrasonic dissolution, the mixed solution was stirred for 1 h, and then poured into 100 mL polytetrafluoroethylene reaction axe, and hydrothermally reacted at 180 ° C for 10 h. The obtained black product was centrifuged at high speed, washed with ultrapure water 3 times, and dried at 60 ° C for 24 h to obtain a CoSe2 / rGO composite catalyst, which was recorded as CSR50.

[0051] An OFX aqueous solution with a concentration of 20 mg / L was prepared, 10 mg of the catalyst was added to the OFX solution (50 mL, 20 mg / L), and stirred in the dark at room temperature for 30 min to reach adsorption-desorption equilibrium, potassium persulfate was added to the above mixture to make its concentration 2 mM, and the visible light source was provided by a metal halide lamp with a 420 nm cutoff filter. Subsequently, 3.0 mL of the solution was taken out every 5 min and filtered through a 0.22 μm filter, and the concentration of OFX was measured at a wavelength of λ=292 nm using a UV-visible spectrophotometer (UV-2600).

[0052] Example 2

[0053] The only difference from Example 1 is that the amount of GO added is 100 mg, and the rest is the same as Example 1. The product is recorded as CSR100.

[0054] Example 3

[0055] The only difference from Example 1 is that the amount of GO added is 150 mg, and the rest is the same as Example 1. The product is recorded as CSR150.

[0056] Characterization and performance testing

[0057] 1) GO (Jiangsu Pioneer Nanomaterials Technology Co., Ltd.) was added to water, ultrasonically dissolved to form a yellow-brown solution, poured into a 100 mL polytetrafluoroethylene reaction axe, and subjected to a second hydrothermal reaction at 180 °C for 10 h. The obtained product was centrifuged at high speed, washed with ultrapure water for 3 times, and dried at 60 °C for 24 h to obtain rGO.

[0058] The morphology of CoSe2, GO, rGO and CSR150 samples was analyzed by FESEM. Figure 1 Shown are FESEM images of (ab) CoSe2; (c) GO; (d) rGO; (ef) CSR150.

[0059] like Figure 1 As shown in a and b, CoSe2 is composed of multiple rods that self-assemble on the surface into a compact baseball morphology. Figure 1 As shown in c, GO is a thin layer with irregular morphology. Figure 1 In the middle (d), GO naturally wrinkles and forms flexible rGO after hydrothermal reaction, with a rough and irregular curled surface. The large specific surface area is conducive to providing abundant reactive active sites for photocatalytic reactions. e and f are the microscopic morphologies of the material CSR150. It can be found that CoSe2 baseballs are deposited on the rough surface of rGO. After the hydrothermal process, rGO wraps CoSe2 inside to form a strong heterojunction interface.

[0060] 2) Figure 2In the figure, (ac) HRTEM images of CSR150; (dh) EDS element mapping spectrum of CSR150; Figure 2 As shown in a and b, it can be clearly found that CoSe2 is encapsulated in rGO, and the two are densely bound to each other. Figure 2 The lattice spacing of c is 0.34nm and 0.27nm, which are attributed to rGO and CoSe2, respectively. Figure 2 In the data, EDS elemental mapping confirmed that the CSR150 material is composed of four elements: C, O, Co and Se, and they are evenly distributed on the catalyst surface.

[0061] 3) Figure 3 In the figure, (ab) XRD patterns of GO, rGO, CoSe2 and CoSe2 / rGO composites; (c) Raman spectra of CoSe2, GO, rGO and CSR150; (d) XPS full spectrum scan; (e) C1s; (f) O1s; (g) Co2p; (h) Se3d and (i) UV-VisDRS spectra of CoSe2, rGO and CoSe2 / rGO composites.

[0062] exist Figure 3 In a, the diffraction peaks at 2θ belong to the 001 (11.29°) and 100 (42.16°) crystal planes of GO. GO contains a large number of oxygen functional groups, which are easily reduced to form reduced graphene oxide (rGO) in high-temperature hydrothermal treatment. Therefore, the diffraction peaks at 24.43° and 43.22° are the (002) plane of rGO and the (100) plane of the carbon rhombus structure, respectively, indicating that GO was successfully reduced to rGO. Figure 3Figure b shows the XRD spectra of different materials. It can be clearly observed that the main peaks of the prepared CoSe2 material in the XRD phase structure mode correspond to the diffraction peaks of the standard card (PDF#89-2003) without obvious deviation. Therefore, the main characteristic diffraction peaks at 29.56°, 30.72°, 34.38°, 35.85°, 47.62°, 50.21° and 53.33° correspond to the (011), (101), (111), (120), (211), (002) and (031) crystal planes in the CoSe2 standard card. In addition, a small number of small peaks can still be seen, but the peak intensity is very low, which further indicates that the purity of the prepared materials is very high. The XRD peak positions of the composite materials CSR50, CSR100 and CSR150 are close to those of pure CoSe2, indicating that the introduction of rGO will not affect the crystal structure of CoSe2, indicating the successful preparation of CoSe2 / rGO composite materials. However, no diffraction peaks of rGO were clearly seen in the composite material, which may be attributed to the fact that the attached CoSe2 prevented the restacking of carbon sheets, so the characteristic diffraction peaks of the layered structure disappeared. The molecular structure and composition of the material were studied by Raman spectroscopy. Figure 3 In c, CoSe2 has a peak at 184 and 668 cm -1 There are strong peaks at g and A 1g The D band is used to reflect the degree of defects in carbon materials, which may be caused by vacancies, heteroatom doping, etc., while the G band represents an ordered, crystalline, and graphite structure. The peak intensity ratio of the D band and the G band (I D / I G ) is often used as an indicator of surface defects and disorder in carbon materials. By breaking the OO bond in PMS, it is beneficial to obtain more defect sites on the carbon layer, which is beneficial to the activation process of PMS. It is worth noting that the D band values ​​in GO and rGO increase from 1359cm -1 and 1345cm -1 The double resonance is generated at 1596cm -1 and 1586cm -1 Therefore, the I D / I G The values ​​are 0.9 and 1.1 respectively, and the peak intensity ratio (I D / I G ) changes from 0.9 to 1.1, which further indicates that GO is reduced to rGO and more vacancy defects are generated on the surface of the material. The five Raman peaks in the composite CSR150 are located at 184 cm -1 (A g )、466cm -1 (E g)、664cm -1 (A 1g )、1349cm -1 (D belt) and 1586cm -1 (G band), and I D / I G The value is 1.2, which is significantly higher than that of GO and rGO, further indicating that the composite material is successfully synthesized and that a large number of defects are formed in the composite material, providing sufficient reactive sites for PMS activation, thereby improving the catalytic reaction activity.

[0063] XPS was used to reveal the surface chemical state and element valence state of CoSe2, rGO and CSR150 materials. Figure 3 Figure d is a full spectrum scan, from which it can be observed that the composite material contains C, O, Co and Se element signals, which is consistent with the EDS element mapping results. Figure 3 Figure 5 shows the high-resolution spectrum of C1s, with binding energies at 283.2, 284.8, and 285.9 eV, which are attributed to CH, C=C / CC, and CO bonds, respectively. In addition, a C=O bond with a binding energy of 288.4 eV was observed in rGO. Figure 3 In (f), the binding energies at 531.1 and 533.0 eV correspond to the oxygen vacancies and C-OH bonds adsorbed on the surface of the material, respectively. Figure 3 The image in g shows a complex pattern. It is possible that the main 2p orbital peak of Co is separated into 2p 3 / 2 and 2p 1 / 2 Two peaks. The binding energy in the CSR150 sample is 780.7 (Co 2+ )、778.8(Co 0 ) and 782.5(Co 3+ ) is attributed to the 2p 3 / 2 track, at 793.8 (Co 0 )、796.4(Co 2+ )、798.1(Co 3+ ) and 801.4eV(Co 3+ ) peak is attributed to 2p 1 / 2 In addition, the peaks at 785.1, 787.5 and 803.9 eV in CSR150 and the peaks at 785.5 and 802.6 eV in CoSe2 are satellite peaks of Co.

[0064] The XPS spectrum of Se3d is as follows Figure 3 As shown in h, the binding energy is 54.4 (3d 5 / 2 )、55.2(3d 3 / 2 ) and 56.0eV(3d 5 / 2) belongs to the Co-Se bond. In addition, the binding energy at 59.4 eV may be due to the oxidation of selenium atoms on the sample surface. Moreover, the XPS binding energies of Co2p and Se3d in CSR150 are generally shifted to the positive direction by 0.5 eV and 0.3 eV respectively compared with CoSe2. Combining the XPS analysis results of the above two materials, it shows that CoSe2 has a weak electron conversion to rGO, which causes the electron cloud density of the rGO layer wrapped on the surface of the material to change, inducing electron redistribution to reconstruct the charge of the surface structure of the CSR150 composite material, releasing more electrons during the photocatalytic degradation of ofloxacin, thereby effectively activating PMS and obtaining excellent catalytic performance (confirmed in the photocatalytic experiment). The optical properties of CoSe2, rGO and CoSe2 / rGO composites were studied by ultraviolet-visible diffuse reflectance spectroscopy (UV-VisDRS). Figure 3 Figure i shows that in the visible light range of 200-800nm, the CoSe2 material absorbs light very stably and broadly. After the introduction of rGO, there is no obvious effect on the light absorption edge of CSR50, CRS100 and CRS150. As the amount of rGO added changes, there are differences in the light response intensity of the composite material.

[0065] Catalytic performance

[0066] 1. The degradation efficiency of the catalyst is evaluated by the following formula:

[0067] Degradation efficiency: (η)% = (1-C / C0) × 100 (1)

[0068] Where C is the TC concentration at different sampling time intervals (t) during the degradation process, and C0 is the initial concentration of TC when the adsorption-desorption equilibrium is reached.

[0069] The apparent rate constant of OFX degradation was calculated by fitting the pseudo-first-order equation (Eq. 2) to evaluate the degradation efficiency of the catalyst under different conditions:

[0070]

[0071] Figure 4 (a) Catalytic degradation effect of OFX under different conditions; (b) -ln(C t / C0) as a function of reaction time during the degradation process; (c) rGO doping effect on the catalytic degradation of OFX and (d) first-order kinetic curve.

[0072] Figure 4 The catalytic conditions are the same as those in Example 1: 10 mg of catalyst, 20 mg / L of OFX aqueous solution, and 2 mM of potassium persulfate.

[0073] like Figure 4As shown in a, the OFX degradation efficiency in the systems of PMS, rGO / PMS, CSR150 and CSR150 / Vis is negligible. However, with the addition of catalysts and changes in conditions, the degradation effect changes significantly, and the degradation efficiencies of CoSe2 / PMS, CoSe2 / PMS / Vis and CSR150 / PMS systems reach 70%, 85% and 91%, respectively. This result confirms that the construction of CoSe2-rGO greatly improves the catalytic performance of CoSe2. With the introduction of visible light, the degradation efficiency is further improved, and the CSR150 / PMS / Vis system has the highest degradation efficiency (97%) within 40 minutes. Figure 4 Figure b shows the k value as a function of the reaction time in the degradation process corresponding to figure a. It can be found that compared with other systems, k in the CSR150 / PMS / Vis system is 0.01534 min. -1 is the highest, further indicating that the degradation efficiency of the CSR150 / PMS / Vis system is the fastest, which is 1.5 times that of CoSe2 / PMS. Figure 4 Figures c and d show that as the rGO incorporation amount gradually increases from 50-150 mg, the corresponding kinetic rate is the fastest, which increases the degradation efficiency of OFX to 97%. The results show that the increase in the doping amount of rGO provides enough reactive active sites to a great extent, contributing sufficient photoelectron flow for the efficient activation of PMS.

[0074] 2. According to the catalytic steps of Example 1, CSR150 catalyst was used to change the PMS concentration, catalyst dosage and OFX concentration in the CSR150 / PMS / Vis system to study the effects of the above conditions on the degradation effect.

[0075] Figure 5 Effects of different conditions (a) PMS concentration; (b) catalyst dosage (catalyst concentration is 0.1-0.6 g / L); (c) OFX concentration; and (d) solution pH value on the degradation effect of the CSR150 / PMS / Vis system.

[0076] like Figure 5 Figure a shows that as the PMS concentration increases from 0 mM to 2 mM, the OFX degradation efficiency increases with the increase in PMS activity, indicating that the number of active groups in the system reaches the optimal catalytic condition. Figure 5 Figure b shows that when the PMS concentration is 2 mM, the degradation efficiency of OFX is significantly improved when the catalyst dosage increases from 0.1 g / L to 0.2 g / L. When it increases to 0.6 g / L, the degradation effect of OFX decreases slightly. The results show that the OFX removal rate still maintains efficient PMS activation within the dosage range. Figure 5Figure c further shows that when the OFX concentration is 10, 20, 30 and 40 mg / L, the degradation efficiency is 98%, 97%, 91% and 87%, respectively. Even at a concentration of 40 mg / L, the removal efficiency of OFX by CSR150 catalyst is still as high as 87%, which confirms that the catalytic performance of CSR150 / PMS / Vis system is very excellent. Finally, considering the catalytic performance and economic factors, the optimal catalytic conditions were determined to be 2mMPMS, 0.2g / L catalyst and 20mg / L OFX.

[0077] The initial solution pH is the main factor affecting the surface charge of the catalyst, which affects the catalytic activity of the catalyst and the existence form of OFX. a1 and pK a2 The values ​​of 5.97 (carboxylic acid) and 9.28 (piperazine ring) are respectively. OFX is positively charged at low pH. The pH value of the catalytic system is adjusted by sulfuric acid or sodium hydroxide, such as Figure 5 As shown in Figure d, the stability of the catalyst was explored in the pH range of 3-11. It was found that the OFX degradation efficiency decreased slightly under strong acidic conditions (pH = 3.0) or high alkalinity (pH = 11.0). This may be because low pH values ​​cause the protonation of the piperazine moiety or carboxylic acid group of OFX and reduce its reactivity to free radicals, while under alkaline conditions (pH = 11.0), the main type of PMS is So5 2- , which increases the electrostatic repulsion between the positively charged catalyst surface and PMS. In addition, these results confirm that the CSR150 catalyst has high catalytic activity over a wide pH range.

[0078] 3. According to the catalytic process of Example 1, different water sources were obtained from the physical environment for investigation, mainly including (from Henan Xinxiang Medical College): river water (Zhaoding River, Riverwater), lake water (Lake water), tap water (Tap water), and the removal effect of OFX was compared with the laboratory deionized water (Ultrapure water).

[0079] Figure 6 (a) The degradation effect of CSR150 catalyst on different water sources; (b) The degradation comparison of different pollutants by CSR150 catalyst; (c) The effectiveness cycle experiment of CSR150 catalyst; (d) The effect of different anions in CoSe2 / rGO / PMS / Vis system on the degradation performance of OFX.

[0080] from Figure 6It can be concluded that the degradation effect of OFX is slightly reduced in river water and lake water, and is significant in tap water and deionized water. This may be because river water and lake water contain some impurities that complex part of the catalyst, which reduces the effect. In general, the prepared catalyst has significant catalytic activity and strong anti-interference in the real water environment, providing an application strategy for actual water treatment.

[0081] In addition, different types of pollutants were selected for universal investigation. The pollutants were tetracycline (configured with deionized water at 20 mg / L), metronidazole (configured with deionized water at 20 mg / L) and methyl orange (configured with deionized water at 20 mg / L). 10 mg of CSR150 catalyst was added to the above pollutant solutions respectively. After 30 minutes of dark reaction, potassium persulfate was added and visible light was introduced for catalytic experiments.

[0082] Figure 6 The results in Figure b show that under the same catalytic conditions, the degradation efficiencies of tetracycline, metronidazole and methyl orange were 98.5%, 100.0% and 99.9% respectively within 40 min. The CSR150 catalyst showed high efficiency in removing other common organic pollutants.

[0083] Figure 6 In the CSR150 catalyst effectiveness cycle experiment, deionized water was used to conduct a cycle experiment to study the extent of metal ion leaching during the entire catalytic process. After four catalytic cycles, the cobalt (Co) leaching concentration was 0.0432 mg / L by inductively coupled plasma optical emission spectroscopy (ICP-OES), further proving that the metal leaching effect of the CSR150 / PMS / Vis system was minimal. Figure 6 Figure c shows that after 4 cycles, the elimination effect of OFX remains good.

[0084] For common anions Cl - 、HCO3 - 、NO3 - and H2PO4 - Anti-interference test was carried out to clarify the influence of anion on OFX degradation ( Figure 6 d). Sodium chloride, sodium bicarbonate, sodium nitrate and sodium dihydrogen phosphate were added to the catalytic system (CSR150 catalyst 10 mg, OFX aqueous solution concentration 20 mg / L, potassium persulfate 2 mM) to make the concentration of each 10 mmol to test the OFX degradation effect. It can be found that the exogenously added NO3 - and H2PO4 - There was no significant effect on the catalytic degradation of OFX, while Cl - and HCO3 - The introduction of HCO3- The inhibitory effect of Cl - Can be connected with SO4 ·- Reacts with ·OH to produce weakly oxidized Cl· and ClOH ·- To reduce the reactivity and as HSO5 - Therefore, when 10mMCl - When entering the system, the degradation efficiency of OFX is reduced by 11%. In addition, HCO3 - In the first 20 minutes of the degradation process, a strong inhibitory effect appeared, which eventually reduced the degradation efficiency of OFX by 13%. One possible explanation is that HCO3 - The degree of hydrolysis of ions in water is greater than the degree of ionization, resulting in an increase in the pH value of the water body. It has been shown that a high pH value has a negative impact on the activation of PMS, so the inhibition becomes more severe as the concentration of added ions increases. - Ions also have the ability to scavenge free radicals and can react with SO4 ·- reaction, further exacerbating the inhibitory effect.

[0085]

[0086] OH+Cl - →ClOH ·- (4)

[0087]

[0088]

[0089] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Application of CoSe2-rGO catalyst in the degradation of ofloxacin, characterized in that: The preparation method of the CoSe2-rGO catalyst comprises the following steps: Mixing Se powder, alkaline reagent and water to obtain a Se-containing mixed solution; Mixing cobalt salt, EDTA-2Na and water to obtain a cobalt salt solution; The Se-containing mixed solution is mixed with a cobalt salt solution to perform a first hydrothermal reaction to obtain CoSe2; Graphene oxide, water and the CoSe2 are mixed to carry out a second hydrothermal reaction to obtain a CoSe2-rGO catalyst.

2. The use according to claim 1, characterized in that: The mass ratio of the Se powder to the alkaline reagent is 0.16-0.32:1.2-3.

6.

3. The use according to claim 1, characterized in that: The mass ratio of the cobalt salt to EDTA-2Na is 0.48-0.95:0.34-0.

73.

4. The use according to claim 2 or 3, characterized in that: The molar ratio of the Se powder to the cobalt salt is 1 to 4:

1.

5. The use according to claim 4, characterized in that: The temperature of the first hydrothermal reaction is 150-180° C. and the time is 12-18 hours.

6. The use according to claim 1, characterized in that: The mass ratio of the graphene oxide to CoSe2 is 50-150:

100.

7. The use according to claim 6, characterized in that: The temperature of the second hydrothermal reaction is 160-180° C., and the time is 10-12 hours.

8. The use according to claim 1, characterized in that: The application method comprises: mixing the CoSe2-rGO catalyst, an OFX-containing solution and peroxymonosulfate, and degrading the obtained mixed solution.

Citation Information

Cited By

  • CoSe nanocrystalline catalytic material and preparation method and application thereof

    CN121338776A

  • Selenide for thermal battery and preparation method and application of diselenide

    CN122426715A